Strategies to Improve Thermal Comfort and Energy Efficiency of Social Interest Housing in Tropical Areas - Adalberto Ospino; Carlos Robles; Ivan Tovar (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
This study focuses on passive measures for thermal comfort in social interest housing in the Departamento del Magdalena, Colombia. The global context emphasises the importance of energy savings, especially in the construction sector, responsible for 40% of global energy use. Despite advances in sustainable construction, social housing in Latin America, particularly in Colombia, neglects thermal efficiency. This paper addresses the lack of regulations and climatic considerations in social housing construction in Colombia, proposing the adoption of passive climate control to improve thermal comfort and air quality. Climate Consultant and EnergyPlus were used to evaluate bioclimatic strategies and local climate impact. Climatic characterisation reveals hot and humid conditions, demanding strategies such as solar protection, cross-ventilation and adaptive measures. Simulations suggest a 61.3% improvement in the annual comfort rate. The study highlights the need to consider the local climatic context and construction strategies to improve energy efficiency and well-being in social housing.